Tunable Fano Resonance and Enhanced Sensing in a Simple Au/TiO2 Hybrid Metasurface - Zhihui He; Weiwei Xue; Wei Cui; Chunjiang Li; Zhenxiong Li; Lihui Pu; Jiaojiao Feng; Xintao Xiao; Xuyang Wang; and Gang Li (Nanomaterials, 2020)
We investigate Fano resonances and sensing enhancements in a simple Au/TiO2 hybrid metasurface through the finite-different time-domain (FDTD) simulation and coupled mode theory (CMT) analysis. The results show that the Fano resonance in the proposed simple metasurface is caused by the destructive interaction between the surface plasmon polaritons (SPPs) and the local surface plasmon resonances (LSPRs), the quality factor and dephasing time for the Fano resonance can be effectively tuned by the thickness of Au and TiO2 structures, the length of each unit in x and y directions, as well as the structural defect. In particular, single Fano resonance splits into multiple Fano resonances caused by a stub-shaped defect, and multiple Fano resonances can be tuned by the size and position of the stub-shaped defect. Moreover, we also find that the sensitivity in the Au/TiO2 hybrid metasurface with the stub-shaped defect can reach up to 330 nm/RIU and 535 nm/RIU at the Fano resonance 1 and Fano resonance 2, which is more than three times as sensitive in the Au/TiO2 hybrid metasurface without the stub-shaped defect, and also higher than that in the TiO2 metasurface reported before. These results may provide further understanding of Fano resonances and guidance for designing ultra-high sensitive refractive index sensors.